Testing of weak form efficiency on Bursa Malaysia’s selected industries / Muhammad Azim Kamil Suhaimi - Kamil Suhaimi, Muhammad Azim (Faculty of Business and Management, 2017)
The purpose of this study is to investigate the existence of Efficient Market Hypothesis in Bursa Malaysia’s selected industries. The data was collected in for each industry for daily, weekly and monthly basis from year 2011 to 2015. This study used Autoregressive Model to regress the past stock price with the current stock price. Result of this study reveals that for daily data, all of the industries has significant relationship which can be concluded as inefficiently weak. Meanwhile, for weekly data only consumer industry is inefficiently weak and for monthly data only industrial industry is inefficiently weak. All the other data for other industries can be concluded as efficiently weak. These results provide understanding towards investors, analysts and regulator in dealing with Efficient Market Hypotheses.